Effectiveness of Digital Media Content on the Behaviour Domain of the Diabetic Patients (Indian Journal of Extension Education, 2020)
The success of diabetes care relies mainly on patients’ daily self-care activities and provider’s continuous support. Diabetes, therefore, is a disease in which transmission of disease-related knowledge and skills from the patient’s perspective will help to build the right attitude in self-management of the disease that can be achieved through education. Hence educating diabetic patients for effective self-management through digital media would be a significant contributor to the metabolic and psychological outcomes of the patients. The study aimed to assess the effectiveness of digital media content on the behavior domain of diabetic patients with two hundred type-2 diabetes respondents from the rural and urban areas of the Guntur district of Andhra Pradesh was conducted. A two months education program based on digital media content in different forms like 90 text, 30 voice messages, and 8 animation modules was developed and disseminated. After the education program, post-intervention changes in the knowledge, skill, and attitude of the respondents was measured with a time gap of two months. The findings revealed that the post-intervention mean score for the knowledge domain scored high in all three areas of information followed by attitude and skill. There existed a highly significant difference at pre and post-intervention with a p-value of 3.29E-06. Further, highly significant difference was also observed among knowledge, skill & attitude of the respondents with a p value of 3.67E-11. Among different areas of information in the KSA domain, the mean score difference was found to be highest for clinical followed by nutrition and for management information. The significant improvement in the KSA domain for all three areas after post-intervention may be due to the dissemination of information by using different content formats such as text, voice messages, and animation modules. Thus, digital education in vernacular language to reach all sorts of patients would be effective for self-management of the disease.